The Belabaja Philosophy in Realizing Sustainable Peace: A Phenomenological Study of the Galiau Watang Lema Traditional Alliance in Alor Regency - Syarifuddin Darajad; Arifin; Muhammad Abdullah; Siti Asiyah; Alfi Raihanah (Universitas Muhammadiyah Surakarta, 2026)
Objective: This study aims to understand and analyze the meaning of the Belabaja philosophy in realizing sustainable peace in the Galiau Watang Lema Traditional Alliance community in Alor Regency. The object of the study focuses on the practice, values, and meaning of the Belabaja ritual as a customary mechanism in reconciling social conflicts and forming the collective identity of the Alor-Pantar coastal community. Theoretical framework: The theoretical framework of this study is based on sociological conflict theory and symbolic interactionism, which views conflict as an inherent part of social dynamics. Literature review: The literature review discusses social conflict as an inherent social process within plural societies and highlights the importance of local wisdom in conflict resolution and reconciliation. Previous studies on customary law, ritual-based reconciliation. Methods: This study uses a qualitative approach with a phenomenological design. Data were collected through participant observation, in-depth interviews with traditional and community leaders, and documentation of traditional practices, then analyzed qualitatively to capture the lived experiences and social meanings attached to the Bela Baja ritual. Results: The results of the study indicate that Belabaja functions as a traditional oath ritual that transforms subjective awareness of solidarity into objective awareness of social brotherhood, thus effectively preventing recurring conflicts and strengthening social cohesion across groups. Implications: The implications of this study confirm that the integration of local wisdom such as Belabaja contributes to the achievement of SDG 16 (Peace, Justice, and Resilient Institutions) and SDG 11 (Sustainable Communities). Novelty: The novelty of this study lies in the phenomenological analysis of Belabaja as a foundation for sustainable peace and collective identity in the traditional alliance system